TERAMPIL BERBICARA DENGAN MODEL SAVIBeL BAGI MAHASISWA TUNADAKSA DI PERGURUAN TINGGI - Linda Eka Pradita; Rani Jayanti; Asih Andriyanti Mardliyah; Engkin Suwandana (MATAPENA: Jurnal Keilmuan Bahasa, Sastra, dan Pengajarannya, 2021)
This study aims to improve speaking skills through the development of the SAVIBeL learning model by taking into account the characteristics and learning principles of students with special needs with disabilities in higher education. This research is motivated by the learning needs of students with disabilities, especially in terms of providing appropriate educational services for them. Apart from the needs of students, it is also motivated by the needs of lecturers as teachers of students with special needs requiring reference learning models which can be accepted not only by students with special needs but also by regular students. This research method uses research and development to develop the SAVIBeL model in learning language skills which includes the syllabus and lesson plans. This study also uses qualitative methods to observe various phenomena that occur and the techniques used are participatory observation techniques and quantitative methods to test the effectiveness of the model. Through research and development methods in developing learning models through analysis of the needs of students and lecturers. The results showed that the role of developing the SAVIBeL model in improving productive language skills, especially speaking skills. The SAVIBeL learning model developed has six learning components, namely syntagmatic learning steps consisting of preliminary, core and closing activities, social systems, reaction principles, support systems, instructional impacts, and accompaniment impacts. Keywords: disability, learning model, savibel